“Determinación de parámetros físico – mecánico y químico del a fibra del ramio (boehmeria nivea) producidos en la provincia de San Martín - Escudero Saldaña, Robert (2003)
The present paper work, titled "Determination of Physical - Mechanic and Chemical Parameters on Ramie Fiber (Soehmeria nívea) Cultivated in the Province San Martin", it was begun firstly with the sowing of Ramie plant in area on 200 square meters in the l.S.T. NOR ORIENTAL DE LA SELVA- BANDA DE SHILCAYO, located at 300 meters on sea level, average temperatura 28ºC, relativa humidity 79% and annual rainy precipitation 1178 mm, as same as chemical and physical - mechanic components were determined in the laboratories of ANACOMPA ANO TEPANAL OF AGRODINDUSTRIAL engineering faculty of SAN MARTIN NATIONAL UNIVERSITYTARAPOTO and laboratory of POCA (AMERICAN SHEEP ANO CAMEL PROGRAM), UNALM - LIMA. lts objective were: • To determine the Physical - Mechanic and Chemical parameters on ramie tiber (Boehmena nívea) cultivated in the province San Martín. • To evaluate the Physical - Mechanic and Chemical parameters on ramie fiber in two growth stages and three maceration times. • To propose the probable use in the textile industry. Two ramie samples (Boehmeria nívea) were used on 2 and 4 months ofo crop and 3 maceration treatments (15, 20 and 30 days), being this raw material used for obtainment of fiber, adapting to the design in Block Completely at Random as same as ANVA showed that had differences between themselves by means of DUNCAN'S Test (0.05), the sample A2B3 (with 4 months of crop by 30 days of maceration), being this the very best with content of cellulose (89.78%) and the sample A1B1 (with 2 months of crop by 15 days of maceration) presents as a result of diameter 24.93μ, length 3.11 inch (78.99 mm), resistance to the fracture 103.53 per 1000 pound I square inch and elasticity 109.00 GF., fron fiber being these the very favorable .. The Chemical and Physícal - Mechanic components on sample of 2 months are: Cellulose 86.17%, Hemicellulose 9.09%, Lignine 11.29%, Estractibles 4. 91 % and ashes 1.89%. lts Physical - Mechanic propertles: Diameter 26.24μ, Lengthe 2.92 inch (74.14 mm), Resistance to the Fracture 97.66 per 1000 pound I square inch and Elasticity 99.33 GF. The sample on 4 months are: Cellulose 88.88%, Hemicellulose 5.. 82%, Lignine 11.9%, Extractibles 6.53% and ashes 1.93%. lts Physical - Mecchanic properties: Diameter 26.67μ, Length 2.65 inch (61.31 mm), Resistance to the Fracture 93.41 per 1000 pound /square iinch and Elasticity 94.00 GF. The results obtained in agreement to analysis realized was for the best sample on 2 months of crop by 15 days of maceration, decause this has properties most appropriate for the testile industry.